1994
DOI: 10.1002/eji.1830240832
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of the ligand for CD40 in newborn lymphocytes

Abstract: Immune responses in newborn lymphocytes show a defect in isotype switching from IgM to IgG and IgA. Immunoglobulin isotype switching in B lymphocytes requires a contact-dependent signal from T lymphocytes which is delivered by the ligand for the B cell surface antigen CD40. We investigated the capacity of newborn lymphocytes to express the CD40 ligand and to undergo CD40 ligand-dependent immunoglobulin isotype switching. After stimulation by phorbol ester and ionomycin, newborn lymphocytes expressed markedly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 30 publications
1
37
1
Order By: Relevance
“…It is generally regarded as an activation marker (28). However, we and others (1,27,29,30) did not find other markers of activation in neonatal cord or infant blood, such as increased expression of CD25, HLA-DR, CD69, and CD154 (CD40 ligand). Nor did we find an increase of thymocyte-like CD1a ϩ or CD4 ϩ /CD8 ϩ double-positive T cells.…”
Section: Discussioncontrasting
confidence: 62%
“…It is generally regarded as an activation marker (28). However, we and others (1,27,29,30) did not find other markers of activation in neonatal cord or infant blood, such as increased expression of CD25, HLA-DR, CD69, and CD154 (CD40 ligand). Nor did we find an increase of thymocyte-like CD1a ϩ or CD4 ϩ /CD8 ϩ double-positive T cells.…”
Section: Discussioncontrasting
confidence: 62%
“…Two potential molecules are CD40L and IFN␥. First, as CD40L is poorly expressed by activated neonatal CD4 ϩ T cells, 18,[56][57][58][59][60] we hypothesized that mature levels of CD40L on activated donor CD4 ϩ T cells were necessary for the development of neonatal antidonor T-cell responses. However, when neonates were exposed to CD40L Ϫ/Ϫ donor cells, they were able to develop vigorous antidonor CTL and Th1/Th2 responses ( Figure 7A and data not shown), demonstrating that donor CD40L is not necessary for the development of neonatal allospecific T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IL-4 production by umbilical cord blood mononuclear cells is consistently described as lower than that from adult peripheral blood mononuclear cells, irrespective of the stimulus used (14,20). The lack of IL-4 and/or CD40 ligand may be the limiting factor in IgE production by the neonate, as a number of investigators have found that exogenous IL-4 in conjunction with CD40 cross-linking increased IgE production by umbilical cord blood mononuclear cells (13,14,16,17).…”
mentioning
confidence: 99%
“…Neonatal B-cell expression of CD40 is similar to the adult (12), and responses to CD40 stimulation can be induced (13,14). Expression of CD40 ligand (CD40L, CD154) is variably described as reduced or comparable to the adult, depending upon the stimulation used (12,13,(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%